Reinterpretation of Justice in Islamic Inheritance Rights Based on Gender - Sholihah, Hani; Nani Widiawati2, Nani; bin Hj. Awang Damit, Mohd Khairul Nazif (al-'adalah, 2024)
The concept of gender justice is often understood from contradictory perspectives. In religion, this issue is notably found in the division of inheritance rights. The interpretation of gender justice in inheritance is polarized between textual and contextual patterns, with approaches that are difficult to reconcile. This paper aims to construct a new meaning of gender justice in inheritance. This theme is examined through qualitative research, literature review design, and analysis based on theories of justice and equality. The research results conclude that the reinterpretation of gender justice in inheritance distribution is implicitly contained. Although there is gender inequality in inheritance distribution, this inequality demonstrates justice. The implications of this research are expected to provide an understanding that equality is not synonymous with justice, so when the distribution of inheritance between men and women is unequal, it does not necessarily mean it is unfair.